Research progress of RhoGTPase activating protein in epithelial-mesenchymal transition - XU Qian, DUAN Hua, GAN Lu, LIU Qiwei (Jichu yixue yu linchuang, 2023)
Epithelial-mesenchymal transition (EMT) is a process by which epithelial cells undergo morphological changes to gain a mesenchymal cell phenotype and migratory properties. As a class of negative regulators of RhoGTPases, RhoGTPase activating proteins(RhoGAP) can bridge between cell surface receptors and cellular actin cytoskeleton during EMT procedure, which may influence cancer cell transition and outcome of fibrotic diseases and may help search for anti-tumor and anti-fibrotic managements.